Oral Anticoagulants in Women: What's the Difference? A Narrative Review - Elena Maria Faioni M.D; Barbara Scimeca M.D (Clinical and Applied Thrombosis/Hemostasis)
Gender sensitive medicine refers to the need to individualize epidemiology, diagnosis, knowledge of disease presentation, and therapy based also on sex and gender. An impressive amount of scientific literature deals now with sex and gender differences in disease. Not so much, yet, on individualized therapeutic approaches. Part of the reason lies in how studies that deal with the pharmacology, efficacy and safety of drugs are conducted. Often women are under-represented, and/or no gender specific analysis of outcomes is performed. As a consequence, in many fields of medicine, not as much is known about important and life-saving drug dosage, safety and efficacy in women as in men. Oral anticoagulants are not the exception, even if new regulations are operative regarding inclusion of women in all phases of drug studies. The result is that there are many areas of uncertainty or outright confusion regarding the efficacy and safety of oral anticoagulants in women that need to be addressed.